Roosting Habitat Use and Selection By Northern Spotted Owls During Natal Dispersal. Issue 2 (30th December 2014) - Sovern, Stan G.; Forsman, Eric D.; Dugger, Katie M.; Taylor, Margaret
ABSTRACT We studied habitat selection by northern spotted owls (Strix occidentalis caurina) during natal dispersal in Washington State, USA, at both the roost site and landscape scales. We used logistic regression to obtain parameters for an exponential resource selection function based on vegetation attributes in roost and random plots in 76 forest stands that were used for roosting. We used a similar analysis to evaluate selection of landscape habitat attributes based on 301 radio‐telemetry relocations and random points within our study area. We found no evidence of within‐stand selection for any of the variables examined, but 78% of roosts were in stands with at least some large (>50 cm dbh) trees. At the landscape scale, owls selected for stands with high canopy cover (>70%). Dispersing owls selected vegetation types that were more similar to habitat selected by adult owls than habitat that would result from following guidelines previously proposed to maintain dispersal habitat. Our analysis indicates that juvenile owls select stands for roosting that have greater canopy cover than is recommended in current agency guidelines. Published 2014. This article is a U.S. Government work and is in the public domain in the USA.